Intact archeological human bones and age at death studied with transmission x‐ray diffraction and small angle x‐ray scattering. (26th October 2021) - Park, Jun‐Sung; Laugesen, Malene; Mays, Simon; Birkedal, Henrik; Almer, Jonathan D.; Stock, Stuart R.
Abstract: High‐energy, wide‐angle x‐ray scattering (WAXS, x‐ray diffraction) and small‐angle x‐ray scattering (SAXS) were used to study intact human second metacarpal bones (mc2) from two UK archeological sites. A novel method correcting for irregular mass distribution was applied in these transmission geometry experiments done at beamline 1‐ID of the Advanced Photon Source. The authors asked whether there were age‐at‐death‐related changes in carbonated apatite (cAp) lattice parameters and whether SAXS could detect collagen D‐period peaks in the archeological mc2. For each of the two sites, Ancaster and Wharram Percy in England, six female mc2s were studied; for each site, two were from each of three age‐at‐death cohorts (young, 18–29 years; middle, 30–49 years; old ≥50 years) along with a modern control mc2. The Rietveld method was applied to the WAXS patterns to provide precise lattice parameter values. The cAp lattice parameters did not correlate with age‐at‐death estimated from dental wear. From WAXS and the 00.2 diffraction peak widths, four archeological mc2s possessed coherently scattering domain lengths (crystallite c ‐axis sizes) that matched that of the modern mc2; SAXS revealed the same four archeological mc2 had D‐period peak intensities equivalent to that of the modern mc2. The other eight archeological mc2s had significantly larger crystallite sizes (than the modern mc2) and weak or absent D‐period peaks, differences attributed to diagenetic changes. Based on these data, the authors suggest that WAXS 00.2 peak width and SAXS D‐period peak intensity can be used with intact bones to select those likely to retain largely unaltered tissue nanostructure, which might be required for other analyses. Taken as a whole, the results suggest detecting age‐related deterioration in nanostructural features may be difficult in bone showing significant bioerosion.